Cutaneous manifestations of systemic non‐Hodgkin lymphomas (NHL): study and review of literature. (24th June 2013) - Carlesimo, M.; Narcisi, A.; Rossi, A.; Saredi, I.; Orsini, D.; Pelliccia, S.; Aloe Spiriti, M.A.; Mari, E.; Cox, M.C.
Abstract Systemic non‐Hodgkin lymphomas are often accompanied by cutaneous manifestations, which are not always looked out for. Nevertheless, these alterations can be very important because their presence is lied to the clinical behaviour of the underlying malignancy, with an early recognition being fundamental. The aim of this study was to make order in this topic and propose a preliminary classification of the cutaneous manifestations associated with non‐Hodgkin lymphomas. We performed a retrospective chart review of 62 haematological patients affected by non‐Hodgkin systemic lymphomas with dermatological manifestations, who were evaluated from January 2007 to December 2011, and combined these results with a systematic review of Pub medical literature from 1937 to 2011 on this topic. A preliminary classification of these manifestations has been proposed, dividing them in specific and non‐specific ones, along with a description of the clinical features and those cases observed in our department. A preliminary approach has been proposed for the study of these manifestations that could be helpful in understanding the biological behaviour and aid early recognition of a flare up in systemic non‐Hodgkin lymphomas.